Marketing Strategy Analysis of Cracker Products in Ganeas - Faiz, Agus Maulana; Anarki, Aprillia Alling; Miftahudin, Miftahudin; Sopandi, Nur Irfan; Purwanti, Tira (SINTESA, 2024)
Kerecek, a traditional snack from Ganeas, Sumedang, has great potential for development in the modern market. However, the product faces several challenges, such as limited innovation, inadequate promotion, and competition with modern snacks that are more convenient and diverse. This study aims to identify factors affecting the competitiveness of kerecek and to design strategies to enhance its appeal in the market. The research method used is qualitative descriptive with interviews and literature review as data collection tools. The results indicate that factors such as lack of innovative flavors, weak branding, and limited distribution are major obstacles in marketing kerecek. Based on these findings, it is recommended to diversify products, improve quality, strengthen promotion through social media, and expand distribution networks to a wider market. With these steps, it is expected that kerecek can become more competitive and popular among modern consumers while maintaining its traditional value as aunique local product